5(x+3)+2=5(x-8)-3x

Simple and best practice solution for 5(x+3)+2=5(x-8)-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+3)+2=5(x-8)-3x equation:


Simplifying
5(x + 3) + 2 = 5(x + -8) + -3x

Reorder the terms:
5(3 + x) + 2 = 5(x + -8) + -3x
(3 * 5 + x * 5) + 2 = 5(x + -8) + -3x
(15 + 5x) + 2 = 5(x + -8) + -3x

Reorder the terms:
15 + 2 + 5x = 5(x + -8) + -3x

Combine like terms: 15 + 2 = 17
17 + 5x = 5(x + -8) + -3x

Reorder the terms:
17 + 5x = 5(-8 + x) + -3x
17 + 5x = (-8 * 5 + x * 5) + -3x
17 + 5x = (-40 + 5x) + -3x

Combine like terms: 5x + -3x = 2x
17 + 5x = -40 + 2x

Solving
17 + 5x = -40 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
17 + 5x + -2x = -40 + 2x + -2x

Combine like terms: 5x + -2x = 3x
17 + 3x = -40 + 2x + -2x

Combine like terms: 2x + -2x = 0
17 + 3x = -40 + 0
17 + 3x = -40

Add '-17' to each side of the equation.
17 + -17 + 3x = -40 + -17

Combine like terms: 17 + -17 = 0
0 + 3x = -40 + -17
3x = -40 + -17

Combine like terms: -40 + -17 = -57
3x = -57

Divide each side by '3'.
x = -19

Simplifying
x = -19

See similar equations:

| 3x+0-12=0 | | 3x^2+9x=6 | | 5(x-3)+2=5(x-8)-3x | | 54x^4-16x=0 | | -20x+10=-6-12x | | x=-6x^2-8x+10 | | y=-6x^2-8x+10 | | 2/3H-1/H+11=8 | | 8y-3=5y+3 | | 6x^2-2x=28 | | -x^2-6x-15=0 | | (24x-18)(4x+3)= | | 13+2(2x-2)=16-3x-7 | | y+4x=7 | | 4x^2+2x=28 | | 7(2a-b)-5(2b-7a)= | | 10=x+15 | | 2=11-3x | | 4x+1.2=6 | | -5x+2=46 | | X^3+6x^2+6x=0 | | 3/n=15/80 | | -8x+80=8x-80 | | 9b+13=14-2b | | 7y-13=22 | | 9b+13=13-2b | | 600y-240=143 | | (-a-5b+6)2ab= | | x^2-2s-26=0 | | 3x+7=-2x+12 | | 4x-x^7+5x^3= | | y=(8*0)-2 |

Equations solver categories